2017
DOI: 10.5812/ijcp.5716
|View full text |Cite
|
Sign up to set email alerts
|

Association Between NAT2 Polymorphisms and Prostate Cancer

Abstract: Background: NAT2 enzyme involved in bioconversion of aromatic amines, heterocyclic arylamines and certain drugs into electrophilic ions that can be important initiators in tumorigenesis process. Objectives: The aim of this study was to assess the possible association between NAT2 polymorphisms (857 G > A, 481 T > C, and 590 G > A) and risk of prostate cancer (PC). Methods: Totally, 207 benign prostate hyperplasia (BPH) and 147 PC Iranian patients were evaluated. NAT2 genotypes were detected by restriction frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Regarding the theoretical correlation between NAT2 SNPs and cancer, a variety of reports have been published to date [12,[48][49][50]. Among these, the data described by Zou et al reported that NAT2 gene polymorphism rs1799931 was associated with decreased risk of AML and was likely to be a protective factor against AML development [12].…”
Section: Phase 11 Genetic Polymorphisms Most Frequently Associated Wi...mentioning
confidence: 99%
“…Regarding the theoretical correlation between NAT2 SNPs and cancer, a variety of reports have been published to date [12,[48][49][50]. Among these, the data described by Zou et al reported that NAT2 gene polymorphism rs1799931 was associated with decreased risk of AML and was likely to be a protective factor against AML development [12].…”
Section: Phase 11 Genetic Polymorphisms Most Frequently Associated Wi...mentioning
confidence: 99%